Modelling of Tsunami Waves (MATEMATIKA, 2008)
The nonlinear dispersive model based on the forced Korteweg-de Vries equation (fKdV) is developed from the approximation of Boussinesq shallow water type model. This provides the possibility of observing, in particular, the process of tsunami generation by atmospheric disturbances. The fKdV is then solved numerically via an explicit finite difference method. From the simulations, the roles of nonlinearity, dispersion and forcing terms in the process of tsunami generation are shown explicitly. Keywords: Tsunami waves; forced Korteweg-de Vries equation; finite difference method.